Aktualisasi Nilai Bela Negara Mahasiswa Asrama Bela Negara UPN “Veteran” Jawa Timur - Leticia Nuzululita Agustine; Sri Wibawani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Defending the country is the right, duty, and responsibility of the people to protect and guarantee the sovereignty of the country based on the people's love for life and the country. The form of defending the country that can be carried out by the younger generation is by carrying out the basic values ​​of defending the country which include love of the country, awareness of the nation and state, believing in Pancasila as the state ideology, being willing to make sacrifices and having the initial ability to defend the country so that by having this attitude it will become a person. a nation with national knowledge and love of the homeland. UPN